Bewertung der Nutzungspotentiale einer Bergbaufolgelandschaft unter dem Aspekt des wirtschaftlichen Strukturwandels der Niederlausitz. - Bahn-Bernsee, Heike (My University, 2007)
Die Arbeit beinhaltet eine Nutzungspotenzialbewertung einer Bergbaufolgelandschaft (BFL). Mit Hilfe einer zielorientierten Nutzwertanalyse werden die Potenziale Landschaft, Infrastruktur, Wirtschaft, Arbeitsplätze, Ökologie und Nachfrage bewertet und die Gunstfaktoren des Untersuchungsgebietes (UG) herausgestellt, um mögliche Handlungsvorschläge zu geben. Leitbild des UG ist eine den gegebenen Bedingungen entsprechende nachhaltige Entwicklung einer BFL. Eine einst vom Abbau der Braunkohle lebende Region sucht ein neues Gesicht und Möglichkeiten, die durch den Tagebaubetrieb völlig veränderten Bedingungen der Landschaft, Infrastruktur, Wirtschaft, Arbeitsplätze, Ökologie, Nachfrage neu zu formieren. In einer eigens für diese Untersuchung entworfenen Matrix werden die Bewertungsergebnisse räumlich veranschaulicht. Das UG besitzt sehr günstige ökologische Potenziale, die bei der weiteren Entwicklung unbedingt berücksichtigt werden sollten. Als wenig günstig stellt sich das Potenzial der Wirtschaft heraus. Das bedeutet, dass besonders Anstrengungen zur Verbesserung der wirtschaftlichen Basis in diesem Gebiet unternommen werden müssen. Die Autorin stellt Möglichkeiten der touristischen Nutzung vor und plädiert für die Nutzung alternativer Energien und nachwachsender Rohstoffe. Im UG muss Mut zu neuen Wirtschaftsstrukturen bewiesen werden. Je vielfältiger die neuen Möglichkeiten genutzt werden, desto stabiler wird die wirtschaftliche Basis. Die ökologische Gunst sollte von Anfang an bei der Gestaltung der Wirtschaft und der Entwicklung neuer Infrastruktur berücksichtigt werden. Mögliche Ausgänge der Entwicklung werden in Szenarien beschrieben, in denen die gegebenen Bedingungen in einer überspitzen Form weitergedacht werden, um das Wesentliche der möglichen Entwicklung darzustellen. Das Besondere der BFL sollte nicht nur als geschichtliche Erinnerung, sondern als raumprägendes Element erkennbar bleiben. difu

This thesis presents an evaluation of the utilization potential of an area previously exploited by open cast mining (post-mining landscape, PML). Utilization potentials such as landscape, infrastructure, economy, jobs, ecology, and demand are evaluated by means of multicriteria analysis. Favourable factors of the study area will be emphasized in order to suggest adequate actions. Guiding principle for the study area is the sustainable development of the PML under the given circumstances. A region once dependent of mining brown coal is looking for a new look as well as for possibilities to restructure landscape, infrastructure, economy, jobs, ecology, and demand based on the completely changed conditions after open cast mining. The results of the evaluation will be presented in a spatially explicit way using special matrix models developed by the author. Coupled with a presentation of mathematically structured results in the sustainability triangle it will be clarified, which economic, social, and ecologicalconditions have to be expected in the study area. In particular by displaying the results in a matrix form it can be shown, which potential parameters are exceptionally favourable, where they occur, and which combination of parameters positively affecting potentials appear in which location. The study area will not develop uniformously, but centres of development can be identified along a node-axis structure. Both economy and social relations as centres of growth will be specially promoted in the nodes. The axes extend along the infrastructural development beyond the margins of the study area, thus providing links to the neighbouring regions. The study area has got a very favourable ecological potential which should be taken into consideration under any circumstance with respect to future development. On the other hand, the economic potential turns out to be less advantageous. Therefore special efforts have to be made in this field to improve the economic basis. Poor economic conditions will rapidly lead todeclining social conditions. The study area is located in a region, which is characterised by an ongoing drain of workforce. Therefore it is important to create a strong and diverse economy. Because of the complete loss of the former economic basis, the mining of brown coal, new methods have to be developed to emphasize the ecological potential of the study area. So called flagships should make the area economically attractive once again and provide new prospects for survival. The author introduces possibilities for touristy use plead simulatneously for using renewable energy and raw material resources. Courage for implementing new economic structures has to be proved. The more the multifaceted novel possibilities will be utilised, the more sound will be the economic basis. The more the economic basis is solidified, the more advantageous will be the effects on the social conditions. Ecological priorities should be considered right from the start in the development of economy and new infrastructure. This will be approved not least by demand. Possible results of development are described in scenarios in which given conditions are deliberately extended in an exaggerated way to demonstrate the essentials of feasible development. Special properties of the PML should not only be observable as historical commemoration, but also as a landscape shaping element.
Evaluation of utilization potential of post-mining landscape with special reference to structural changes in economy in Lower Lusatia.
Keywords: Landschaft; Braunkohlebergbau; Strukturwandel; Regionalwirtschaft; Kulturgeographie; Bewertungskriterium; Infrastruktur; Ökologie; Arbeitsmarkt; Fremdenverkehr; Szenario; Rekultivierung; Landschaftsplanung; Bergbaufolgelandschaft; Landschaftsnutzung; Nutzungskonzept; Nachhaltigkeit